Multiple and Independent Phases of Transposable Element Amplification in the Genomes of Piciformes (Woodpeckers and Allies) - Manthey, Joseph D (Genome Biol Evol, 2018)
The small and conserved genomes of birds are likely a result of flight-related metabolic constraints. Recombination-driven deletions and minimal transposable element (TE) expansions have led to continually shrinking genomes during evolution of many lineages of volant birds. Despite constraints of genome size in birds, we identified multiple waves of amplification of TEs in Piciformes (woodpeckers, honeyguides, toucans, and barbets). Relative to other bird species’ genomic TE abundance (< 10% of genome), we found ∼17–30% TE content in multiple clades within Piciformes. Several families of the retrotransposon superfamily chicken repeat 1 (CR1) expanded in at least three different waves of activity. The most recent CR1 expansions (∼4–7% of genome) preceded bursts of diversification in the woodpecker clade and in the American barbets + toucans clade. Additionally, we identified several thousand polymorphic CR1 insertions (hundreds per individual) in three closely related woodpecker species. Woodpecker CR1 insertion polymorphisms are maintained at lower frequencies than single nucleotide polymorphisms indicating that purifying selection is acting against additional CR1 copies and that these elements impose a fitness cost on their host. These findings provide evidence of large scale and ongoing TE activity in avian genomes despite continual constraint on genome size.